Pengembangan Komik Digital “Aku Anak Sholehah, Aku Berempati” sebagai Media Pembelajaran PAI Siswa Kelas 2 Sekolah Dasar - Widi Prastika, Deninggar; Mazidah, Ninik; Fahri Ali, Muhammad; Putranta, Himawan (IIQ An Nur Yogyakarta, 2024)
This article examines the problems that arise from technological advances that have a major impact on the world of education. Continuously developing technology has changed the way learning media are used and reduced students' interest in literacy. Literacy interest is a key element in the learning process, especially at the elementary school level. To overcome educational challenges in the 21st century, researchers developed digital comic learning media